The prevalence of ocular manifestations in road traffic accidents treated at a rural tertiary care hospital in south india: a cross sectional study - Menon, Liji; Mani, Soman; Mathew, Anna (International Journal of Research in Medical Sciences, 2017)
Background: Ocular injuries following road traffic accidents (RTA) is one of the common causes of ophthalmological morbidity and unilateral blindness. The aim of this study was to document the epidemiological pattern of ocular injures caused by RTA in a cross-sectional population brought to a tertiary care centre in rural southern India. Methods: After receiving institutional ethics committee approval, all patients over the age of 10 years, who came to the emergency department (ED) of this rural tertiary care centre with alleged history of RTA, during the period, July-December 2015 were serially enrolled to participate in the study after obtaining written informed consent. The sample size for 95% confidence level and precision of 5% was calculated to be 191. Results: Out of the 832 cases of RTA presenting to the ED, 191 (23%) had ocular injuries. There were 186 (97.38%) closed globe injuries and 5 (2.6%) open globe injuries. Eight (4.1%) patients with ocular injuries had no perception of light in the affected eye after the accident. The commonest injury was periorbital edema and ecchymosis (68.6%) followed closely by eyebrow laceration (63.9%) and lid laceration (48.2 %). The commonest anterior and posterior segment injuries were traumatic optic neuritis (6.3%) and vitreous or retinal haemorrhage 4 (2.09%) respectively. Conclusions: In this study, the prevalence of ocular involvement in RTA was is 23%. Most of the injuries were closed globe injuries and periorbital edema and ecchymosis were the commonest type of injury occurring followed by eyebrow and lid laceration.